Research Trends of Augmented Reality in Physics Education based on Scopus Database in Thirteen Years (2010-2023): A Bibliometric Approach - Nurjanah, Siti; Iqbal, Muhammad; Sultan, Jumriani; Sholihin, Sholihin; Ulyasari, Nur; Rashid, Salman (STKIP Singkawang, 2024)
This research is useful for mapping the development of AR research in physics learning. This research is a bibliometric study to analyze scientific publications related to the implementation of Augmented Reality (AR) in physics learning. Data obtained from the Scopus database by applying certain inclusion criterias, resulting in 55 relevant publications from 2010 to 2023. Data analysis is done using Rstudio application with biblioshiny package. The analysis is done to extract a variety of bibliometric information such as publication trends, authors and influential countries, keywords, themes, and research trends. The analysis shows a significant increase in publications since 2017, with Germany and Indonesia as the most research countries. The integration of AR into learning methods like PBL is found to be the most dissected. Inter-country and inter-affiliate research collaboration on this topic still needs to be enhanced. Existing research is largely focused on the potential of augmented reality to enhance students' interest, motivation, and understanding of physical concepts through interactive and realistic visualizations. These findings could inform the direction of future research to produce significant innovations in improving the quality of physics learning.